Brucella melitensis 16MΔhfq attenuation confers protection against wild‐type challenge in BALB/c mice. (16th July 2013) - Zhang, Junbo; Guo, Fei; Chen, Chuangfu; Li, Zhiqiang; Zhang, Hui; Wang, Yuanzhi; Zhang, Ke; Du, Guoqing; li, Yuefeng; Wang, Jiangde; Jian, Tong; Wang, Zhen
ABSTRACT Brucellosis is a globally distributed zoonotic disease that causes animal and human diseases. Although effective, the current Brucella vaccines (Rev.1 and M5‐90) have several drawbacks. The first involves residual virulence for animals and humans and the second is the inability to differentiate natural infection from that caused by vaccination. Therefore, Brucella melitensis 16M hfq mutant (16MΔhfq) was constructed to overcome these drawbacks. Similarly to Rev.1 and M5‐90, 16MΔhfq reduces survival in macrophages and mice and induces strong protective immunity in BALB/c mice. Moreover, these vaccines elicit anti‐Brucella‐specific IgG1 and IgG2a subtype responses and induce secretion of gamma interferon and interleukin‐4. The Hfq antigen also allows serological differentiation between infected and vaccinated animals. These results show that 16MΔhfq is an ideal live attenuated vaccine candidate against virulent Brucella melitensis 16M infection. It will be further evaluated in sheep.